MOBA Metamorphosis: The Evolution of Gamer Preferences in the MOBA Esport Landscape in Indonesia - Muhammad Yovie Ridwan; Muhamad Riyan Maulana (Journal Innovation in Information and Computer Technology, 2024)
This research examines the shift in player preferences from Mobile Legends to Honor of Kings (HOK) in Indonesia, which reflects significant changes in the MOBA esports industry. This research aims to understand the factors that influence this shift in interest and its impact on the esports industry. The research methods used include social media content analysis and participatory observation in gaming communities to collect qualitative data. The results showed that the uniqueness of HOK's gameplay, boredom with Mobile Legends, and positive influence from influencers and the HOK community were the main drivers of players' interest switch. This research confirms that changing player preferences reflect the evolving dynamics of the video game industry, in which marketing strategies and gameplay innovation play an important role. The findings provide valuable insights for game developers and industry stakeholders in the face of future market changes and consumer behaviour.